Thermodynamics of Ligand Binding to a Heterogeneous RNA Population in the Malachite Green Aptamer - Sokoloski, Joshua E. (2011)
The malachite green aptamer binds two closely related ligands, malachite green (MG) and tetramethylrosamine (TMR), with near equal affinity. The MG ligand consists of three phenyl rings emanating from a central carbon, while TMR has two of the three rings connected by an ether linkage. The binding pockets for MG and TMR in the aptamer, known from high-resolution structure, differ only in the conformation of a few nucleotides. Herein, we applied isothermal titration calorimetry (ITC) to compare the thermodynamics for binding of MG and TMR to the aptamer. Binding heat capacities were obtained from ITC titrations over the temperature range of 15 to 60 °C. Two temperature regimes were found for MG binding: one from 15 to 45 °C where MG bound with a large negative heat capacity and an apparent stoichiometry (n) of ~0.4, and another from 50 to 60 °C where MG bound with positive heat capacity and n~1.1. The binding of TMR, on the other hand, revealed only one temperature regime for binding, with a more modest negative heat capacity and n~1.2. The large difference in heat capacity between the two ligands suggests that significantly more conformational rearrangement occurs upon the binding of MG than TMR, which is consistent with differences in solvent accessible surface area calculated for available ligand-bound structures. Lastly, we note that binding stoichiometry of MG was improved not only by raising the temperature, but also by lowering the concentration of Mg(2+) or increasing the time between ITC injections. These studies suggest that binding of a dynamical ligand to a functional RNA requires the RNA itself to have significant dynamics.